Захист віртуальних машин на основі інструкцій нового покоління процесорів AMD Zen - Соколовський, В.С.; Карпінець, В.В.; Яремчук, Ю.Є.; Присяжний, Д.П.; Приймак, А.В. (Реєстрація, зберігання і обробка даних, 2018)
Розглянуто можливість використання спеціалізованого криптографічного ядра процесора AMD Zen PRO для підвищення захисту віртуальних машин від несанкціонованого доступу, зокрема, через мережу Інтернет. Запропонований метод дозволяє виконувати шифрування та дешифрування захищених сторінок оперативної пам’яті на апаратному рівні, що забезпечує стійкість віртуальних машин до багатьох активних атак, а також дозволяє підвищити їхню швидкодію в цілому. Наведено приклад реалізації запропонованого методу для операційної системи Windows 10. Рассмотрено возможное использование специализированного криптографического ядра процессоров AMD Zen PRO для повышения уровня защиты виртуальных машин от несанкционированного доступа, в том числе через сеть Интернет. Предлагаемый метод разрешает выполнять шифрование и расшифровку защищенных страниц оперативной памяти на аппаратном уровне, что обеспечивает устойчивость виртуальных машин ко многим активным атакам, а также позволяет повысить их производительность в целом. Предложен пример реализации вышеуказанного метода для операционной системы Windows 10. It is demonstrated the development of a virtualization environment security subsystem with the help of hardware-accelerated AMD Zen CPU cryptography API and its instruction set for security tasks, including but not limited to: protection against unauthorized memory access, data leaks, hypervisor breach, external attacks and malware spread via the Internet. The method in question utilizes real-time memory encryption and decryption, with the memory bandwidth and computing power sufficient for seamless hypervisor and server operation, virtual machine live migration and secure export, and demonstrates capabilities of ARM Cortex A5 on-board cryptography processor core for mentioned tasks, as well as providing secure asymmetric key exchange invisible and inaccessible to any software beside internal Trusted Platform Module and its inner DRAM memory controller, to guarantee high level of virtual environment security and sufficient resistance to most active attacks with minimum computation overhead, suitable for most real-life virtualization-based workload scenarios. The example subsystem specifically targets Microsoft Windows 10 operating system, however software support for different operating systems (including UNIX-based) may already be provided by appropriate vendors, including enterprise-ready solutions, such as Cisco, Dell, HP, etc.